Evaluation of hematological markers as prognostic tools in rheumatoid arthritis - Maryam Masoumi; Maryam Bozorgi; Zahra Nourmohammadi; Mohammad Javad Mousavi; Aref Shariati; Jafar Karami (BMC Rheumatology)
Abstract Background Reducing inflammation is central to the management of RA. However, commonly used markers such as CRP and ESR, along with the DAS-28 score, have shown limitations. Hematologic indices, such as platelet-lymphocyte ratio (PLR), lymphocyte-monocyte ratio (LMR), and neutrophil-lymphocyte ratio (NLR), show potential as reliable indicators of inflammation in RA. This study evaluates these markers across different RA activity levels to identify effective biomarkers for distinguishing active RA from remission. Materials and methods 305 RA patients were enrolled in our study, diagnosed by ACR/EULAR 2010 criteria, and divided into four groups according to the DAS28-ESR score. 8 ml of blood were taken for a CBC test and serological tests such as rheumatoid factor (RF), anticyclic citrullinated peptide antibodies (anti-CCP), anti-nuclear antibodies (ANA), and C-reactive protein (CRP). Platelet-lymphocyte ratio (PLR), lymphocyte-monocyte ratio (LMR), and neutrophil-lymphocyte ratio (NLR) were assessed as potential markers of inflammation. Results The mean age of RA patients was 51.7 years and a disease duration of 56.7 months. Significant differences in tender and swollen joints were observed between RA groups. Laboratory findings revealed higher CRP and ESR in active RA patients, while hemoglobin, hematocrit, and lymphocyte counts were higher in remission group. ROC analysis showed ESR, CRP, NLR, and PLR as potential markers for distinguishing active from remission RA, with ESR demonstrating the highest diagnostic accuracy. LMR could not differentiate between active and inactive forms of RA disease. Conclusion The NLR and PLR markers were significantly correlated with traditional inflammatory markers like CRP and ESR. These novel markers could be useful tools for evaluating RA activity, offering a cost-effective alternative to imaging techniques. Further research is needed to confirm their clinical utility.